A portable CRISPR Cas12a based lateral flow platform for sensitive detection of Staphylococcus aureus with double insurance. (February 2022) - Qian, Jiajie; Huang, Di; Ni, Desheng; Zhao, Jiarun; Shi, Zhuwei; Fang, Mengjun; Xu, Zhinan
Abstract: Foodborne pathogens cause many food safety problems and Staphylococcus aureus ( S. aureus ) is one of them that seriously threaten human health through the ages. The conventional methods for S. aureus detection basically include culture-based methods and polymerase chain reaction, which are somewhat time-consuming and laborious, and require infrastructure and professional operations. In this article, a portable and visible detection platform for S. aureus was established based on CRISPR/Cas12a, which integrated with nucleic acid isothermal amplification, CRISPR/Cas12a detection, and lateral flow strips for final signal readout. The nuc gene specific in S. aureus and conservative 16S rDNA fragment in Staphylococcus genus were selected as the detection targets. The CRISPR detection platform achieved the sensitivity of 1 × 10 0 CFU/reaction of S. aureus in pure culturing samples and performed well in the specificity assay, while the sensitivity of 2 × 10 1 CFU/mL of S. aureus was obtained in artificially contaminated food samples. Consequently, this platform combined ultra-sensitivity, specificity, accuracy, portability, user-friendliness, and time-saving, which fulfills the actual requirements in the point-of-care testing of S. aureus and was also promising for further applications in the detection of other foodborne pathogens. Highlights: CRISPR/Cas12a based lateral flow method for Staphylococcus aureus was established. Nuc and 16S rDNA were selected as the targets for double insurance. Results can be sensitively observed by naked eyes within an hour.